(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2022)
On-farm demonstration of improved emmer wheat varieties was conducted in Sinana and Goba districts of Bale Zone. The main objective of the study was to demonstrate and evaluate recently released Haydaro variety along with standard check. The demonstration was under taken on single plot of 10 m x 10 m area for each variety with the spacing of 20 cm between rows and recommended seed rate of 150 kg ha-1 and fertilizer rate of 100 qt ha-1 NPS. Mini-field day involving different stakeholders was organized at each respective site. Yield data per plot was recorded and analysed using descriptive statistics, while farmers’ preference to the demonstrated varieties was identified using focused group discussion and summarized using pair wise and simple ranking methods. The demonstration result revealed that Haydaro variety performed better than the standard check of Sinana 01 variety with an average yield of 33.5 qt ha-1, while that of the standard check was 27.2 qt ha-1. Haydaro variety had 23.16% yield advantage over the standard check. The farmers in all districts selected this variety. Thus, Haydaro variety was recommended for further scaling up in the selected area. Int. J. Agril. Res. Innov. Tech. 12(1): 1-3, June 2022